Oncologic Impact of Conservative Treatment Compared with Surgical Treatment of Anastomotic Leakage Following Colorectal Cancer Surgery: A Retrospective Study - Junichi Sakamoto; Atsuko Tsutsui; Chie Hagiwara; Go Wakabayashi (Journal of the Anus, Rectum and Colon)
Objectives: Differences in oncological outcomes between conservative and surgical treatments for anastomotic leakage (AL) in patients undergoing colorectal cancer surgery remain unclear. Methods: From July 2011 to June 2020, 385 patients underwent curative resection with double-stapling anastomosis for left-sided colon and rectal cancers. Among them, 33 patients who experienced AL were retrospectively evaluated and categorized into two groups: conservative (n = 20) and surgical (n = 13). In the surgical group, abdominal lavage using a sufficient amount of normal saline was performed during reoperation. The primary endpoint was the 3-year cumulative incidence of local recurrence (LR). Results: Seven (21.2%) patients in the conservative group experienced LR, while none in the surgical group. Survival analysis indicated no differences in overall and recurrent-free survival. However, the 3-year cumulative incidence of LR was significantly lower in the surgical group than in the conservative group (0% versus 31.3%, p=0.045). Conclusions: Differences in AL management were associated with oncological outcomes, specifically a decreased LR. Therefore, surgeons should consider our findings when determining the most appropriate AL treatment to improve oncological outcomes.